The role of gut microbiota in the occurrence and progression of non-alcoholic fatty liver disease - Mai, Huanzhuo; Yang, Xing; Xie, Yulan; Zhou, Jie; Wang, Qing; Wei, Yiru; Yang, Yuecong; Lu, Dongjia; Ye, Li; Cui, Ping; Liang, Hao; Huang, Jiegang (Frontiers in Microbiology, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent cause of chronic liver disease worldwide, and gut microbes are associated with the development and progression of NAFLD. Despite numerous studies exploring the changes in gut microbes associated with NAFLD, there was no consistent pattern of changes. Method: We retrieved studies on the human fecal microbiota sequenced by 16S rRNA gene amplification associated with NAFLD from the NCBI database up to April 2023, and re-analyzed them using bioinformatic methods. Results: We finally screened 12 relevant studies related to NAFLD, which included a total of 1189 study subjects (NAFLD, n = 654; healthy control, n = 398; obesity, n = 137). Our results revealed a significant decrease in gut microbial diversity with the occurrence and progression of NAFLD (SMD= -0.32; 95% CI -0.42 to -0.21; P < 0.001). Alpha diversity and the increased abundance of several crucial genera, including Desulfovibrio, Negativibacillus, and Prevotella, can serve as an indication of their predictive risk ability for the occurrence and progression of NAFLD (all AUC > 0.7).The occurrence and progression of NAFLD are significantly associated with higher levels of LPS biosynthesis, tryptophan metabolism, glutathione metabolism, and lipid metabolism. Conclusion: This study elucidated gut microbes relevance to disease development and identified potential risk-associated microbes and functional pathways associated with NAFLD occurrence and progression.